Automatic Voice Recorder Designing as A Project-Based Learning Implementation To Enhance Skills In Designing Aeronautical Telecommunications Facilities - Bayu Astika, I Made; Toni, Toni; Tohazen, Tohazen; Agung Ayu Mas Oka, I Gusti (Edukasi Islami: Jurnal Pendidikan Islam, 2023)
Project-Based Learning (PjBL) is a highly engaging active learning model that fosters increased student participation and enhances their problem-solving abilities. Automatic voice recorder design was an output of PjBL undertaken by students in the Air Navigation Engineering diploma four years program, especially in the aviation communication equipment course. One of the learning outcomes of this course is being able to design aviation communication equipment, such as voice recorder. The method used in designing an automatic voice recorder was DDR from Richey and Klein, which consists of design, development and evaluation stages. The results of an automatic voice recorder design trails can be concluded that the design has worked well, but does not fully meet the technical specifications of voice recorder for VHF Air-Ground communication transceiver, including storage capacity, non-interfering playback operations, and accuracy of recording time. The assessment results of the PjBL indicate that all students have successfully attained one of the specified learning outcomes in the aviation communication equipment course, particularly in the area of voice recorder design. This achievement will ultimately contribute to the enhancement of students' skills in designing aeronautical telecommunication facilities.